The Moderation of Financial Discernment In Analyzing The Effect of Audit Opinion, Management Change, and Audit Delay on Voluntary Auditor Switching In Banking Companies Listed on The Indonesia Stock Exchange - Deden Iwan Kusuma (Journal of Social Research, 2025)
In Indonesia, the development of public companies is one of the influencing factors for the emergence and development of the public accounting profession. This study aims to analyze the influence of audit opinions, management changes, and audit delays on voluntary auditor switching by moderating the variables of financial difficulties. This study is focused on banking companies listed on the Indonesia Stock Exchange (IDX) for a certain period. The research method uses moderation regression analysis with secondary data obtained from the company's annual report. The results show that audit opinions and audit delays have a significant influence on voluntary auditor switching. The change of management did not show a significant influence on the decision to replace the auditor. In addition, the variable of financial difficulties moderated the relationship between audit opinions and voluntary auditor switching, but did not moderate the relationship between audit delay or management change and voluntary auditor switching. These findings provide important insights for banking companies in making strategic decisions related to the selection of external auditors and financial management.